Comparative evaluation of fentanyl versus nalbuphine for attenuation of hemodynamic changes during airway stimulation - Buchh, Aqusa; Gupta, Kumkum; Sharma, Deepak; Anwar, Usman; Pandey, Mahesh Narayan; Kalra, Pavitra (International Journal of Research in Medical Sciences, 2018)
Background: Airway stimulation predictably leads to variable hemodynamic changes which can be modified by opioid premedication. The present study was aimed to compare the clinical efficacy of fentanyl with nalbuphine on hemodynamic changes during airway stimulation. Methods: Sixty adult patients of ASA physical status I and II of either gender, were randomized into two groups of 30 patients each to receive either fentanyl 2µg/kg, Group I or nalbuphine 0.2mg/kg, Group II, 10min before induction with propofol. Direct laryngoscopy and intubation was facilitated with vecuronium bromide. Heart rate, blood pressure and ECG were recorded at baseline, after giving study drug, at intubation and then after at 1st, 2nd, 3rd, 5th, 10th and 15th minutes after intubation and noted as primary variable. Any adverse effects and complications were recorded as secondary end points. Results: After premedication, the fall in heart rate was comparable between the groups. The fall in mean blood pressure showed statistically significant difference between the groups. After induction, there was further decrease in heart rate and blood pressure with statistically significant difference. After laryngoscopy and intubation, the increase in mean heart rate and blood pressure occurred immediately in patients of nalbuphine group and persisted up to 1to 2min while this increase persisted up to 5 to 7min in fentanyl group. The differences in hemodynamic changes between the groups were statistically significant. Conclusions: Nalbuphine (0.2mg/kg) could effectively attenuate the hemodynamic changes during airway stimulation when compared to fentanyl (2µg/kg), when given 10 minutes before induction.